Utilization of selected leucine peptide amides by Escherichia coli. - Hirshfield, I N (1975)
Studies on the utilization of leucine peptide amides as a source of leucine for a leucine auxotroph showed that in general compounds with the structure leu-chi amide (where chi is any amide) are utilized as well as the free peptide, but that compounds with the structure chi-leu amide (where chi is not leucine) are used less effectively than the free peptide. Growth and enzymological experiments indicated that the lower capacity of Escherichia coli to utilize amides of the structure chi-leu amide is not a result of poor transport of these compounds, but rather the inability to rapidly liberate leucine from the amide when it is supplied to the cell in the form of a peptide. Competition studies indicated that the peptide amides enter the cell via the oligopeptide permease system.